Minimal tooth preparation for posterior monolithic ceramic crowns: Effect on the mechanical behavior, reliability and translucency - Dal Piva, Amanda Maria de Oliveira [UNESP] (2021)
Objective: Despite the increased use of monolithic crowns, their performance has yet to be determined when the minimal tooth preparation (MTP) principle is considered. The goal of this study was to evaluate the effect of MTP on the mechanical behavior, reliability and translucency of posterior monolithic ceramic crowns. Methods: Dentin analogues were machined using two preparation designs (0.5 or 1 mm reduction) to receive first molar crowns in order to evaluate the monolithic crown performance. Next, 126 crowns were divided (21/g) according to the material (High translucent zirconia – YZHT, Zirconia reinforced lithium silicate – ZLS and Hybrid ceramic – HC) and thickness (0.5 or 1 mm). Tensile stress concentration was calculated using the finite element method. The crowns were adhesivelly cemented and step stress fatigued to calculate reliability for missions at 600 and 1000 N. Translucency was analyzed in 10 discs of each material and thickness. Results: Higher stress concentration was found in thinner crowns and those with higher elastic modulus. YZHT crowns were suspended when fatigue reached 1500 N load, thus 1-parameter Weibull was used to analyze the data. Reliability was only affected by thickness at 1000 N. ZLS.5 showed lower survival than HC.5, which was similar to the groups that presented 100% survival. YZHT showed the highest strength and data scattering. ZLS1 (22.3 ± 1.4) presented higher translucency than HC1 (19.2 ± 0.6) and YZHT1 (12.0 ± 2.9), whereas ZLS.5 and HC.5 were similar to each other (26.5 ± 2.3, 26.7 ± 2.2) and superior to YZHT.5 (12.7 ± 1.2). Significance: HC.5 combined high reliability and translucency with low stress concentration, yielding better crown performance and tooth preservation.